2014
DOI: 10.1038/jhg.2014.79
|View full text |Cite
|
Sign up to set email alerts
|

The first case in Asia of 2-methyl-3-hydroxybutyryl-CoA dehydrogenase deficiency (HSD10 disease) with atypical presentation

Abstract: 2-Methyl-3-hydroxybutyryl-CoA dehydrogenase (2M3HBD) deficiency (HSD10 disease) is a rare inborn error of metabolism, and <30 cases have been reported worldwide. This disorder is typically characterized by progressive neurodegenerative disease from 6 to 18 months of age. Here, we report the first patient with this disorder in Asia, with atypical clinical presentation. A 6-year-old boy, who had been well, presented with severe ketoacidosis following a 5-day history of gastroenteritis. Urinary organic acid analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…13 Yet, their overlapping biochemical signature has led to clinical misdiagnosis. 14 HSD10 disease has been reported only in a small number of families world-wide, mostly occurring in males, consistent with HSD17B10 being located on the X-chromosome. 7 DNA sequencing analyses to date have identified 10 missense mutations in HSD17B10.…”
Section: Introductionmentioning
confidence: 94%
“…13 Yet, their overlapping biochemical signature has led to clinical misdiagnosis. 14 HSD10 disease has been reported only in a small number of families world-wide, mostly occurring in males, consistent with HSD17B10 being located on the X-chromosome. 7 DNA sequencing analyses to date have identified 10 missense mutations in HSD17B10.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, his male cousin, who had the same mutation, achieved normal neurodevelopment until his current age of 8 years (Rauschenberger et al 2010). We recently reported another patient with the c.460G>A (p.A154T) mutation who showed no neurological regression until his current age of 6.5 years (Fukao et al 2014). Thus, in this report, we described an additional two patients with c.470C>T (p.A157V) mutations, leading to the atypical presentation of HSD10 disease.…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, immunoblot analysis showed that fibroblasts from patients with p. A157V or p.A154T mutations had similar levels of HSD17B10 protein as control fibroblasts ( Fig. 1) (Fukao et al 2014). These mutations may affect catalytic activity but not stability.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations